Disruption of sscR encoding a γ-butyrolactone autoregulator receptor in Streptomyces scabies NBRC 12914 affects production of secondary metabolites - S. Kitani; M. Hoshika; T. Nihira (Folia Microbiologica, 2008)

Relationship between eyed‐egg percentage and levels of cortisol and thyroid hormone in masu salmon Oncorhynchus masou - M. Mingist; T. Kitani; N. Koide; H. Ueda (Journal of Fish Biology, 2007)
A possible cause of the low eyed‐egg percentage that afflicts pond‐reared masu salmon Oncorhynchus masou at a fish hatchery (Kumaishi Fish Hatchery, Hokkaido, Japan) was investigated. Serum cortisol levels of masu salmon during the spawning period were compared between individuals from Kumaishi and those from another station (Mori). Cortisol, thyroxine (T 4 ) and triiodothyronine (T 3 ) hormones were also measured in eyed eggs and their levels were compared to the eyed‐egg percentage. Serum cortisol levels were significantly higher at Kumaishi than at Mori in May and July of the breeding season. At the Kumaishi station, there was a linear positive relationship between serum cortisol and fertilized‐egg cortisol levels of female masu salmon. As cortisol levels in both ovulating females and eyed eggs increased, the eyed‐egg percentage decreased, indicating a highly significant negative relationship between cortisol levels and eyed‐egg percentage. In contrast, as T 3 and T 4 levels in eyed eggs increased, the eyed‐egg percentage increased. The strong positive correlation between high cortisol levels in serum and in eyed eggs at Kumaishi indicates that the frequently higher cortisol levels may have caused the lowering of the eyed‐egg percentage.

Changes in GnRH levels in the brain and pituitary gland during migrations of sockeye salmon and chum salmon - T. Kitani; S. Matsumoto; H. Yamada; M. Amano; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2003)

A novel synoviocyte line (RAMAK-1), derived from a patient with rheumatoid arthritis - M. Kawakami; S. Matsukuma; M. Hara; T. Hidaka; K. Suzuki; A. Kitani; S. Hiroi; T. Ishizuka; Y. Matsuki; H. Nakamura (In Vitro Cellular & Developmental Biology - Animal, 1998)